THE INFLUENCE OF INVESTMENT OPPORTUNITY SET AND MECHANISME OF CORPORATE GOVERNANCE TOWARDS QUALITY OF PROFIT - Sunarti, Sri; Alfie, Atieq Amjadallah; Astuti, Ernawati Budi (Lembaga Jurnal & Seminar Universitas Pembangunan Panca Budi, 2022)
This study aims to analyze the effect of investment opportunity set, and corporate Gavernance mechanism on earnings quality. This study uses a sample of manufacturing companies in the consumer goods industry sector listed on the Indonesia Stock Exchange during the period 2016 to 2019. The number of companies sampled in this study are 53 companies with 4 years of observation. Based on the purposive sampling method, the total sample of this study was 173 financial and annual reports. The data collection method used is secondary data, obtained from www.idx.co.id and the data analysis used is multiple linear regression analysis which is processed using SPSS 20. Multiple linear analysis includes classical assumption test, hypothesis testing and coefficient of determination. Based on the analysis results show that the investment opportunity set has a significant positive effect on earnings quality, the audit committee has a significantly positive effect on earnings quality, independent commissioners have a significantly negative effect on earnings quality, institutional ownership has no significant positive effect on earnings quality, managerial ownership has no significant negative effect on earnings quality. earnings quality and investment opportunity set and corporate governance mechanism have a significant effect on earnings quality.